Rising Nationalism in the Balkans - LILA, Fejzi (European Journal of Multidisciplinary Studies, 2017)
Balkans consists of the geographic and demographic diversity of the complex, with division of the region into new states, with local antagonisms. Balkan leaders, the Great Powers would urge the expansion of national states where and when he wanted interest and would not ignore claims it was one nation over another. The process of developing the nationalist movements and the state - forming in the Balkans, starting with the Patriarchies autonomous movements within the Ottoman Empire, involves the movement of Serbs, Greeks, Bulgarians, Romanians and Albanians. The fall of Bonaparte in 1815, was accompanied by significant changes in Europe in the system of international relations, the diplomacy of the Great Powers. Europe was thrown into the system the concert of Europe, after that of Vienna, while the Ottoman Empire was beginning its stagnation, other European powers had begun to feel the threat of Russia's interests in the Middle East. During this period of time the nationalist movement took place in the region. The nationalism confronted Concert of Vienna principles provoking the First World War.
Keywords: Balkans, Concert of Europe, Great Powers, nationalism, Ottomans, Russian.